Evidences of seismic events during the sedimentation of Sete Lagoas Formation (Bambui Group - Ediacaran, Brazil) - Okubo, J. [UNESP] (2020)
The Sete Lagoas Formation (Ediacaran), located in the central part of the Sao Francisco Craton (Brazil), consists of limestones and dolostones deposited in very shallow waters in the inner part of the carbonate platform. Four breccia types occur throughout the stratigraphic succession: evaporitic breccia with tepees, flat-pebble breccia, hydrothermal breccia and brecciated stromatolites. Here we combine a detailed sedimentological and stratigraphic analyses of the flat-pebble breccia in order to determine its origin and the processes and environmental conditions that originated these brecciated facies. The studied interval consists of a 20 m thick succession of tabular beds composed of flat-pebble breccia interbedded with laminated microbialites. In these breccia beds, the clasts are usually platy or oblate with angular edges and are mainly disposed horizontally within the sedimentary bed, suggesting that they were not transported or reworked. The presence of microbialite clasts with sharp edges and vertices in the Sete Lagoas flat-pebble breccia suggests that the lithification process started very early in diagenesis and, even the sediments exposed at the bottom were, at least, partially lithified. Some breccia levels show bidirectional imbrication and clast size analyses reveal a NE-SW long-axis clast orientation whereas square clasts tend to fill the space among oriented clasts. Breccia clasts are vertically oriented and show deformation features increasing upwards, typically of deforming beds formed by ascendant expulsion of liquefied sediment. Disrupted layers or presenting folds and synsedimentary faults commonly occur confined between undeformed beds. Other evidences of liquefaction and soft-sediment deformation are the injection structures, as flame and load cast-like features, in the base of the brecciated beds. These structures commonly penetrate the upper bed and disrupt the sedimentary layer immediately above promoting local brecciation. These features are found both in modern and ancient deposits of seismic influence, which suggests a similar origin for the Sete Lagoas flat-pebble breccia. Thus, the processes that led to the formation of the studied flat-pebble breccia are interpreted as seismically triggered, since: a) the breccia beds are laterally continuous and extend for several kilometers; b) the breccia beds are restricted to a 20 m thick stratigraphic interval; c) the clasts of the breccia are the same lithology of non- deformed beds below and above the interval of breccia; d) the interbedding of breccia beds and laminated microbialite beds is recurrent; e) the breccia beds are subhorizontal and present irregular upper and lower contacts; f) the presence of liquefaction structures and dyke injection. Thus, this seismic-triggered breccia deposits represent the product of the synsedimentary tectonism occurred within the Sao Francisco Craton during the terminal Ediacaran and correspond to a very well-defined local stratigraphic marker in the Bambui Basin. The seismic activities could be related to the NW regional faults in the regional Paleoproterozoic basement of the study area, which were reactivated during the deposition of the Sete Lagoas Formation in the Ediacaran Period.